Fifty hats that changed the world - Anderson, Robert, 1966- (Design museum (Conran Octopus Limited), 2011)
Lists the top 50 hats and headwear that have made a substantial impact in the world of fashion and design today. From an early 14th century imperial crown to Noel Stewart's 2010 Ribboned Cityscape headpiece, each entry offers a short appraisal to explore what has made their iconic status and the designers that give them a special place in design history.